Hop, hop, jump! - Thompson, Lauren, 1962- (Margaret K. McElderry Books, 2012)
Rhyming text, accompanied by labeled illustrations that identify parts of the body, encourages readers to wiggle and twist, stomp and zig-zag, and hug and shrug.